The relationship between organizational precursors and employee creativity during COVID-19 pandemic: An examination of the psychological safety mediation effect - May, Amy Yeo Chu; Min, Tan Xuen; Rudiawarni, Felizia Arni (University of Islam Malang, 2022)
The study aims to examine the mediating effect of psychological safety on the relationship between organizational antecedents (corporate social responsibility or CSR, transformational leadership style, and perceived organizational support) and employee creativity. This study lends its support to the mediating effect of psychological safety to inspect the underlying reasons that motivate employees to be more creative. The study employed a positivist approach based on 220 respondents. Data was collected through an online open-ended questionnaire using a convenient sampling technique. The collected data were further analyzed using partial least square structural equation modeling. The key findings reveal that the four domains of CSR (legal, philanthropy, economic and ethical), transformational leadership style, and perceived organizational contribute to creating a climate of psychological safety among employees. This climate, in turn, mediates the relationship between these organizational factors and employee creativity. This study highlights the importance of psychological safety as a mediator that motivates employees to be more creative. The results also underscore the need for organizational leaders to review CSR policies, leadership styles, and the support provided to employees to foster psychological safety and, consequently, stimulate employee creativity.